2022
DOI: 10.1186/s40001-022-00650-x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Mycobacterium tuberculosis using Gene Xpert among tuberculosis suspected patients in Gedeo Zone, Southern Ethiopia

Abstract: Background Tuberculosis (TB) is a communicable disease remains a major global health problem and the leading cause of death from a single infectious agent. Even though many of the WHO recommended TB control strategies were implemented; there is still a major gap in TB case detection and treatment. This study aimed to determine the prevalence of Mycobacterium tuberculosis among presumptive TB patients in Gedeo Zone, Southern Ethiopia. Methods A cros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
4
4
0
Order By: Relevance
“…The present study also revealed that TB-HIV co-infection was found to be high (32.6%) and more likely to be positive for TB compared to patients who were HIV-negatives. This finding is in line with previous studies conducted across the country [ 17 , 20 , 22 , 31 , 32 ]. Similarly, malnutrition was found to be contributing factor to the positivity of M .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study also revealed that TB-HIV co-infection was found to be high (32.6%) and more likely to be positive for TB compared to patients who were HIV-negatives. This finding is in line with previous studies conducted across the country [ 17 , 20 , 22 , 31 , 32 ]. Similarly, malnutrition was found to be contributing factor to the positivity of M .…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the detection rate of M . tuberculosis was significantly higher in males than females, which is also supported by many study reports in developing countries [ 21 , 22 , 26 , 29 , 30 ]. Although, it is not statistically significant, relatively higher prevalence of M .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A study in San Francisco, USA, claimed that GeneXpert MTB/RIF could greatly reduce the frequency and impact of unnecessary empiric treatment or overtreatment by 94% as well as reduce the impact of transmission in household contact, providing substantial patient and programmatic benefits if used for making management decisions [ 27 ]. A cross-sectional study on the use of Xpert-MTB/RIF assay for diagnosis in Southern Ethiopia reported a prevalence of 26.8% among 384 suspected MTB patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a South African study, 14% of participants seek TB advice from herbalists, and 14% self-reported staying at home. Another study in Karachi, Pakistan, found that healthcare professionals in tuberculosis programs lacked expertise, causing some patients to fall behind on treatment and others to take their medications incorrectly 25,26 . In the studies conducted in Ethiopia, the first one included 384 participants suspected of TB, M. tuberculosis was isolated from 103, giving an overall prevalence of 26.8%.…”
mentioning
confidence: 99%